Navigating the uncharted: a case report of ignatzschineria spp. infection in tissue independently of maggots infestation - Mohd Taib, Niazlin; Masri, Siti Norbaya; Ahmad Zaidi, Irda Yuhanis; Mohd Ali, Marlindawati; Mohd Yusoff, Nurul Hafizah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Ignatzschineria spp. are a rare cause of human infection, typically associated with fly larvae infestations in open wounds. Most cases in the literature have reported that Ignatzschineria spp. are usually isolated from blood, urine, and abscess cultures, but not from tissue cultures. We report an interesting case of Ignatzschineria spp. detected in a tissue culture from a 62-year-old woman with diabetes, who had presented with gangrenous toes. She underwent debridement and ray amputation of the toes, before being treated with oral ciprofloxacin for three weeks based on the culture and sensitivity reports.